Criminal responsibility for making deliberately unjust sentence, decision, definition or ruling by a judge (judges): analysis of the main corpus delicti - Козак, В. А. (Problems of legality, 2013)
The article deals with objective and subjective signs of corpus delicti, presupposed by p. 1 Art. 375 of the CC (making deliberately unjust sentence, decision, definition or ruling by a judge (judges), forms conclusions concerning interpretation of several corresponding provisions of the criminal legislation of Ukraine regarding researched problem.